How timely closure can reduce outbreak duration: gastroenteritis in care homes in North West England, 2012-2016 - Thomas Inns; Alex Keenan; Rita Huyton; John Harris; Miren Iturriza-Gomara; Sarah J. O'Brien; Roberto Vivancos (BMC, 2018)
Abstract Background Data on outbreaks of infectious gastroenteritis in care homes have been collected using an internet-based surveillance system in North West England since 2012. We analysed the burden and characteristics of care home outbreaks to inform future public health decision-making. Methods We described characteristics of care homes and summary measures of the outbreaks such as attack rate, duration and pathogen identified. The primary analysis outcome was duration of closure following an outbreak. We used negative binomial regression to estimate Incidence Rate Ratios (IRR) and confidence intervals (CI) for each explanatory variable. Results We recorded 795 outbreaks from 379 care homes (37.1 outbreaks per 100 care homes per year). In total 11,568 cases, 75 hospitalisations and 29 deaths were reported. Closure within three days of the first case (IRR = 0.442, 95%CI 0.366-0.534) was significantly associated with reduced duration of closure. The total size of the home (IRR = 1.426, 95%CI = 1.275-1.595) and the total attack rate (IRR = 1.434, 95%CI = 1.257-1.595) were significantly associated with increased duration of closure. Conclusions Care homes that closed promptly had outbreaks of shorter duration. Care home providers, and those advising them on infection control, should aim to close homes quickly to prevent lengthy disruption to services.